Gestão empresarial na prática: um estudo de caso em uma fábrica de doces em Mossoró/RN - Macedo, Jonas Mike Rocha (Universidade Federal Rural do Semi-Árido, 2018)
In recent times it has been observed that the search for quality has been gaining prominence in organizations, and many are the reasons to invest in the continuous improvement of their production processes. With regard to the food industry, food handling must follow standard manufacturing processes of quality, with a view to the safety and reliability of consumers. Given this context, it is essential to highlight the importance of using methods and tools for quality control, as well as a specialized business management. This research aims to follow the process of implementing a business consultancy in a candy factory, with the general objective of identifying the possible causes of the problems that involve the production sector, applying some of the quality tools as support in the search for continuous improvement. The research method used to carry out this work was the case study carried out in a candy factory, the type of research approach was combined, that is, qualitative and quantitative, a bibliographical survey was also carried out to constitute the theoretical reference, highlighting the subject studied. In the case study, the steps and activities that guided the business consulting process were presented. Thus it was verified that there was a more serious problem in the pre-weighing of raw material, affecting the production. To solve the problem, a machine maintenance plan was suggested, as well as process control worksheets. Lastly, training was developed to adequately fill out the control worksheets, in order to maintain a continuous improvement of the company's processes.
Monografia
Keywords: Gestão empresarial; Controle da qualidade; Consultoria empresarial; Business management; Quality control; Business consulting; ENGENHARIAS::ENGENHARIA DE PRODUCAO